Current Status and Recent Stand Structure Dynamics in Mixed Silver Fir—European Beech Forests in Croatian Dinarides: Are There Differences between Managed and Unmanaged Forests? - Jura Čavlović (Sustainability, 2021)
The environmental, social and economic potential of Dinaric uneven-aged forests along with the complex stand dynamics influenced by different long-term management approaches and environmental factors require comprehensive forest monitoring. This study aimed to explore differences in the current status and recent past dynamics of stand structures between unmanaged and managed mixed fir-beech forests in the Croatian part of the Dinaric Alps using large-scale data from an established monitoring system. From the 74 permanent sample plots distributed within the forest type measured in 2008 and re-measured in 2019, we stratified four strata (types of management regimes): (1) forests out of regular management and tree harvest for at least 30 years, (2) managed state forests on carbonate bedrock, (3) managed state forests on non-carbonate bedrock and (4) managed private forests. In each sample plot, 34 structural attributes were computed to assess indicators of their current status and recent past dynamics of stands in the studied forests. An increasing Q shape diameter distribution with a high number of large and very large trees characterize unmanaged forests and managed forests on non-carbonate bedrock. In managed state forests and private forests, variable (rotated sigmoid) and constant (negative exponential) results were obtained, respectively. Principal component analysis (PCA) distinguished managed and unmanaged forests with decreasing harvest volume and recruitment, increasing basal area, number of very large trees, average diameter at breast height (DBH), crown defoliation of firs and basal area of died beech trees. The current structure, recent and expected stand dynamics in the unmanaged forests (accumulation of standing volume, increase of large diameter trees and large snags, large share of beech, large mean DBH) can be recognized as old-growth attributes. The differences between the studied forest types, potential of both unmanaged and state managed fir-beech forests and approaches to sustain multifunctional forest management in the Dinaric region were discussed.